Being and becoming "fully human" in an HIV-positive world : HIV/AIDS and feminist Christian spirituality - Snyman, D.; Kretzschmar, L. (Acta Theologica, 2008)
Feminists have researched the link between gender and HIV/AIDS and shown that women are not always morally responsible for being HIV-positive. This article contributes to the debate by presenting a systematic discussion of women's experience of HIV/AIDS and spirituality. It offers a model of full humanity that interprets the links between HIV/AIDS, poverty, and gender and uses feminist spirituality as a resource for transformed healing. The model was developed by weaving together the interpreted experiences of black, HIV-positive women participants with the teachings of feminist Christian spirituality. This research study shows that in responding to the HIV/AIDS pandemic, it is necessary to adopt an integrative, multifaceted and holistic approach that embodies the gender perspective so that the fully human spirituality of people and women in particular, is enhanced.
Free
Keywords: AIDS (Disease); Agent (Philosophy); Body; Human – Religious aspects – Christianity; Feminist theology; HIV (Viruses); Open access; Peer reviewed; Self – Religious aspects – Christianity; South Africa – Socio-economic conditions; Spiritual life (Christianity) – 2000; Women – Health; Women – Religious life